(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Introduction: The modern era is witnessing a dramatic increase in the incidence of endocrine disorders. The notorious and the non specific nature of the symptoms many a time leads to clinical misdiagnosis. One such condition is Hypothyroidism. An early accurate diagnosis of hypothyroidism is essential as late management may lead to complications as diabetes, IHD etc. For decades the standard treatment of hypothyroidism is levothyroxine. The side effects of levothyroxine as hair loss, headache, menstrual irregularities etc. are forcing the mankind to go for an alternative treatment. To evolve a good treatment a complete understanding of hypothyroidism on Ayurvedic basis is highly essential. Aim: To understand hypothyroidism according to Ayurveda. Materials & Methods: Ayurvedic Samhitas, modern medical text books and websites. Result: Hypothyroidism can be understood as ‘Amayukta Kaphavruta Udanavata’ according to Ayurveda. Conclusion: Depending on several factors as Dosha, Nidana, Samprapti and Lakshanas hypothyroidism can be understood as Kaphavruta udanavata.